Tight Junctions of the Neurovascular Unit - Hudson, Natalie; Campbell, Matthew (Frontiers in Molecular Neuroscience, 2021)
The homeostatic balance of the brain and retina is maintained by the presence of the blood-brain and inner blood-retinal barrier (BBB/iBRB respectively) which are highly specialised barriers. Endothelial cells forming the lining of these blood vessels are interconnected by the presence of tight junctions which form the BBB and iBRB. These tight junctions, formed of numerous interacting proteins, enable the entry of molecules into neural tissues while restricting the entry of harmful material such as anaphylatoxins, bacteria and viruses. If the tight junction complex becomes dysregulated due to changes in expression levels of one or more of the components, this can have detrimental effects leading to brain and retinal pathology.